ChemInform Abstract: An Efficient One‐Pot Reaction for the Synthesis of Pyrazolones Bearing a Phenothiazine Unit. Issue 7 (22nd February 2013) - Baciu‐Atudosie, Lavinia; Ghinet, Alina; Belei, Dalila; Gautret, Philippe; Rigo, Benoit; Bicu, Elena
Abstract The convenient procedure involves formation of hydrazines from substrates (I) followed by reaction with esters (II).